1998
DOI: 10.1139/e97-122
|View full text |Cite
|
Sign up to set email alerts
|

The falling amplitude of carbon isotopic oscillations through the Lower to Middle Cambrian: northern Siberia data

Abstract: Carbon and oxygen isotopes have been studied in Lower to Middle Cambrian fossiliferous carbonates from sections along the Malaya Kuonamka, Olenek, and Muna rivers of the Yudoma-Olenek facies belt, northern Siberian Platform. Marked temporal oscillations in delta 13C are recorded from shallow-water Nemakit-Daldynian to Atdabanian carbonates, as seen elsewhere on the platform. Rapid sea-level rise during the so-called "Sinsk event" led to starved-basin conditions from the middle Botomian (Bergeroniellus micmacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 26 publications
6
38
0
2
Order By: Relevance
“…Carbon isotope values from the earlier OttawaBochum dataset (Table 3 of Supplementary Material) are consistent with the higher resolution dataset herein, and with published data from Siberia (Brasier & Sukhov, 1998 …”
Section: Results Of the Geochemical Analysessupporting
confidence: 88%
See 2 more Smart Citations
“…Carbon isotope values from the earlier OttawaBochum dataset (Table 3 of Supplementary Material) are consistent with the higher resolution dataset herein, and with published data from Siberia (Brasier & Sukhov, 1998 …”
Section: Results Of the Geochemical Analysessupporting
confidence: 88%
“…2). This is in agreement with data from Brasier & Sukhov (1998) showing a plateau during this interval from the Siberian Platform and with the values oscillating near zero in Laurentia, reported by Saltzman (2005), and China (Zhu et al 2004;Peng et al 2006). Mild oscillations in the Ust'-Brus and Labaz formations (Fig.…”
Section: The Middle-upper Cambrian Boundary In the Kulyumbe Sectionsupporting
confidence: 92%
See 1 more Smart Citation
“…For the Montagne Noire area, southern France, Wotte et al (2007) revealed two minor positive shifts in the lowermost Celtiberian and two stronger ones higher up in equivalents of the Marocconus notabilis Zone. Similar trends have been reported from the Lower-Middle Cambrian transition in Siberia (Brasier et al 1994a, Brasier & Sukhov 1998 and Australia (Donnelly et al 1988, Shergold 1995, Ebneth et al 2001, Lindsay et al 2005. Based on these data, Lindsay et al (2005) proposed direct correlation of early Middle Cambrian δ 13 C trends between the distinct positive excursion in the Ordian-early Templetonian Giles Creek Dolostone of the Amadeus Basin and similar signatures in the coeval middle Gum Ridge Formation of the Georgina Basin, the upper Montejini Limestone of the Wiso Basin, and the upper Tindall Limestone of the Daily Basin with an early Amgan peak in Siberia detected by Brasier & Sukhov (1998).…”
Section: Isotopic Signaturessupporting
confidence: 85%
“…Clearly, a satisfactory GSSP will need to be based on paleontological data. Carbon isotopes may be useful for delimiting the Ediacaran-Cambrian boundary interval and the earliest Cambrian period for which several positive carbon isotope excursions can be detected in various regions (Banerjee et al 1994;Brasier 1985Brasier , 1991Brasier , 1992Brasier , 1994Brasier et al 1990Brasier et al , 1992Brasier et al , 1993Brasier et al , 1994aBrasier et al , 1994bBrasier & Sukhov 1998;Derry et al 1994). Nevertheless, such distinct excursions are largely absent (or not yet recognized) for the second half of the Early Cambrian and the early Middle Cambrian, although several regional studies seem to promise useful results (e.g.…”
Section: Implications For Global Correlationmentioning
confidence: 99%